Solid-state NMR and DNP-Enhanced Solid-state NMR Analysis of Sustainable Materials - McLellan, Alison Daly (2023)
In the drive for more sustainable chemistry, a thorough understanding of the relationship between the structure and properties of any given product is essential. Molecular level characterization is key for optimization of desired properties and synthesis. For many materials, this can be done with high-resolution solution-state techniques or X-ray crystallography. However, to fully understand their structural-property relationships, materials must be studied in the state in which they will be used. Often this state is not amenable to these techniques. In these cases, solid-state NMR provides this vital information. In this work, solid-state NMR analysis has been applied to two classes of materials. Firstly, solid-state NMR was used to probe the defects in hybrid organic-inorganic perovskite materials with potential applications in solar cells. Structural defects in these materials can improve their function but also reduce their stability. To make these perovskite solar cells commercially viable, a thorough understanding of the relationship between the material properties and the dynamics and structural differences caused by these defects is essential. Static and MAS variable temperature 1H NMR has been used to identify possible diffusion of protonic defects in MAPbI3. The second class of materials studied were polymers. For these materials, dynamic nuclear polarization (DNP) enhanced solid-state NMR was used. The low sensitivity of NMR limits its capability to analyse intrinsically dilute aspects of high molecular weight polymers, such as cross-links, chain-ends, and interfaces. DNP-enhanced solid-state NMR has not had the same impact on polymer analysis as it has in biological and materials science. This may be attributed to the discouragingly low enhancements seen and difficult sample handling encountered when using traditional DNP methods on polymers. In this work, the benefits, and disadvantages of two sample impregnation methods for polymer DNP have been shown. Additional benefits of polymer DNP have also been demonstrated. Beyond a simple sensitivity enhancement, DNP has been shown to provide insight to the dynamics of polymer chains and functional groups.